Effects of esketamine and fluoxetine on depression-like behaviors in chronic variable stress: a role of plasma inflammatory factors - Chen, Haixia; Zhao, Xinxin; Ma, Xinxu; Ma, Hongzhe; Zhou, Cuihong; Zhang, Yunyun; Peng, Zhengwu; Xue, Shanshan; Cai, Min (Frontiers in Psychiatry, 2024)
Mounting evidence has identified the rapid and sustained antidepressive and anxiolytic-like effects of esketamine. However, the underlying mechanism of this no-monoamine target rapid-onset antidepressant is still underexplored. Immune-inflammatory pathways and cellmediated immune activation, mainly including inflammatory cytokines in plasma, play a pivotal role in the pathogenesis of major depressive disorder and are also a potential therapeutic target for MDD. The current study was designed to clarify the role of esketamine on the expression of plasma cytokines in a depressive-like model introduced by chronic variable stress (CVS).In this study, a 21-day consecutive CVS exposure produced significant depressive-and anxiety-like behaviors. Both a single dose of esketamine and 7-days repeated fluoxetine administration elicited anti-depressive and anxiolytic effects in mice exposed to CVS.